Defective proviruses significantly impact viral transcription and immune activation in men and women with HIV-1 subtype C in rural South Africa - Buchholtz, Ninée V. E. J.; Hermans, Lucas E.; Umunnakwe, Chijioke N.; Nühn, Marieke M.; Voss, Regina; Need, Emma; Kootstra, Neeltje A.; Maurer, Irma; de Jong, Dorien C. M.; Symons, Jori; Tempelman, Hugo A.; Wensing, Annemarie M. J.; et al. (Frontiers in Immunology, 2024)
IntroductionThe main obstacle to achieving an HIV-1 cure is the proviral reservoir. To promote equity in HIV cure strategies, it is crucial to study the viral reservoir of the predominant HIV-1 subtype C in both women and men. Therefore, we investigated the dynamics of the (intact) viral reservoir in relation to plasma viral load (VL), CD4+ T cell count, and immune activation before and during 96 weeks of successful antiretroviral therapy (ART).MethodsEighty-two participants (62% female) newly initiating ART in a rural clinic in South Africa were included in the study. Blood samples were collected at baseline, week 48, and week 96, and CD4 count was determined. Plasma was used for VL and immune marker analyses, while isolated peripheral blood mononuclear cells (PBMCs) were used for the quantification of cellular multiple spliced HIV-1 RNA (msRNA) and the intact proviral DNA assay. For the longitudinal analyses on ART, we selected only those participants who durably suppressed their VL to <200 copies/mL during 48 (n=65) and/or 96 (n=60) weeks of treatment.ResultsAt ART initiation, the median CD4 count was 234 cells/mm3 and VL was 68,897 copies/mL. Interestingly, at baseline the number of defective proviruses was significantly correlated with VL (p<0.0001), msRNA (p<0.0001), CD4 count (p=0.0008), CXCL10 (p=0.0003) and TNF-α (p=0.0394). During successful ART, a significant decrease of both the intact and defective proviral reservoir was observed (p<0.0001). The decrease of the intact proviral reservoir was more profound compared to the defective fraction after 96 weeks of therapy. In addition, a significant decrease in cellular msRNA and IL-6, IL-7, TNF-α, sCD14, sCD163, CCL2, CXCL10, and CRP was detected.DiscussionThis study underscores the significant relationship observed prior to therapy initiation between the number of defective proviruses, viral transcription/production and their association with immune response indicators such as CD4 count, CXCL10, and TNF-α. Furthermore, the observation of a less pronounced decrease of the defective proviral DNA highlights the importance of addressing both intact and defective proviruses in therapeutic strategies to enhance clinical outcomes for people with HIV-1. Together, these findings suggest a significant role of the defective proviruses in HIV-related disease progression.